2021
DOI: 10.1111/1759-7714.14120
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells (CTCs)/circulating tumor endothelial cells (CTECs) and their subtypes in small cell lung cancer: Predictors for response and prognosis

Abstract: Background The aim of the study was to define the clinical significance of circulating tumor cells (CTCs)/circulating tumor endothelial cells (CTECs) and their subtypes in small cell lung cancer (SCLC) patients. Methods CTCs/CTECs and their subtypes were determined using SE‐iFISH technology in 33 SCLC patients before initial treatment (B1), after two cycles of chemotherapy (B2), at the completion of chemotherapy (B3), and disease progression (B4). The correlations with clinical characteristics, progression‐fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…In addition, our results showed the level of CTECs was higher than the level of CTCs in breast cancer patients. Inversely, other studies reported that CTCs occupied the majority of circulating aneuploid cells in colorectal cancer [ 26 ] and nonsmall cell lung cancer [ 30 ]. A potential mechanism is that epithelial-mesenchymal transition (EMT) and endothelial-to-mesenchymal transition (EndoMT) are generally recognized to be related to cancer cell metastasis, which may proceed diversely in different cancers due to diverse characteristics of the respective blood and lymphatic vessel systems [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results showed the level of CTECs was higher than the level of CTCs in breast cancer patients. Inversely, other studies reported that CTCs occupied the majority of circulating aneuploid cells in colorectal cancer [ 26 ] and nonsmall cell lung cancer [ 30 ]. A potential mechanism is that epithelial-mesenchymal transition (EMT) and endothelial-to-mesenchymal transition (EndoMT) are generally recognized to be related to cancer cell metastasis, which may proceed diversely in different cancers due to diverse characteristics of the respective blood and lymphatic vessel systems [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the high metastatic capacity, the concentration of CTCs in SCLC exceeds that of solid tumor with exception of inflammatory breast cancer by a wide margin (17). This high number of CTCs in SCLC lends itself to the study of the biology of metastatic seeding, including genomic preconditions and tumor cell heterogeneity (18,19).…”
Section: Sclc Ctcsmentioning
confidence: 92%
“…Using subtraction enrichment-immunofluorescence in situ hybridization (SE-iFISH) quantitative analysis, it was found that counting the total number of CTCs and CTECs may help to identify malignant nodules with high sensitivity, while quantifying tetraploid CTCs and CTECs may help to identify malignant nodules with high specificity [ 83 ]. The results showed that the combined detection of specific subtypes of aneuploid CD31 + CTECs and CD31 − CTCs is helpful in effectively identifying malignant nodules in patients with early NSCLC [ 84 ]. The level of CECs in partial response (PR) patients was found to be significantly higher than that of stable disease (SD) or progression disease (PD) patients.…”
Section: Introductionmentioning
confidence: 99%